A Case Report of a Woman with Premenstrual Dysphoric Disorder Misdiagnosed as Having Bipolar Affective Disorder - Rossitza Iakimova; Maya Stoimenova-Popova; Petranka Chumpalova; Milena Pandova; Maria Stoyanova (Journal of Biomedical & Clinical Research)
Frequent mood changes are found in premenstrual dysphoric disorder (PMDD) as well as in bipolar affective disorder (BAD). The differential diagnosis is difficult because both conditions share some other common symptoms.We present a case study of a woman with premenstrual dysphoric disorder misdiagnosed as bipolar disorder. As a result, the patient was prescribed lithium and remained symptomatic for a prolonged period. She recovered only after initiation of treatment with a selective serotonin reuptake inhibitor, which is the treatment of choice in the management of PMDD.In such cases, the importance of affective symptoms evaluation is underscored in the context of the menstrual cycle, as well as in recognizing them for the correct diagnosis and treatment.